2022
DOI: 10.3389/fphy.2022.1013729
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating the cross talk of orbital angular momentum modes in free-space optical communication by using an annular vortex beam and a focusing mirror

Abstract: The probability density analysis formula of the single orbital angular momentum (OAM) mode of an annular vortex beam with a focusing mirror in a turbulent atmosphere is derived theoretically, and the effects of different parameters on the OAM spectrum are investigated numerically, and the results show that the OAM diffusion of the annular vortex beam is weaker than the Gaussian vortex beam in a turbulent atmosphere under the same conditions, and the annular vortex beam with a focusing mirror can more effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…[23] Wang et al explored the focused mirror method and circular aperture method to reduce OAM crosstalk of LG beams in plasma turbulence and demonstrated that the focused mirror method can be used to mitigate the effects of OAM crosstalk from turbulence better than the circular aperture one. [24] Moreover, there are focused annular vortex beams, [25] focused Bessel beams, [26] and other focused vortex beams that have high tolerance to turbulent interference and potentially other properties. [27] Compared to transport media such as atmospheric turbulence, oceanic turbulence is more complex and has a greater impact on the vortex beams passing through it.…”
Section: Introductionmentioning
confidence: 99%
“…[23] Wang et al explored the focused mirror method and circular aperture method to reduce OAM crosstalk of LG beams in plasma turbulence and demonstrated that the focused mirror method can be used to mitigate the effects of OAM crosstalk from turbulence better than the circular aperture one. [24] Moreover, there are focused annular vortex beams, [25] focused Bessel beams, [26] and other focused vortex beams that have high tolerance to turbulent interference and potentially other properties. [27] Compared to transport media such as atmospheric turbulence, oceanic turbulence is more complex and has a greater impact on the vortex beams passing through it.…”
Section: Introductionmentioning
confidence: 99%